Oligocene‐Miocene deformational and depositional history of the Andean hinterland basin in the northern Altiplano plateau, southern Peru. Issue 9 (29th September 2014) - Perez, Nicholas D.; Horton, Brian K.
Abstract Cenozoic basin fill of the northern Altiplano plateau records the tectonic development of the flanking Western Cordillera magmatic arc and Eastern Cordillera fold‐thrust belt. The Ayaviri hinterland basin of southern Peru contains a 2300 m thick succession of fluvial sandstones and overbank siltstones (upper Oligocene Puno Group and lower Miocene lower Tinajani Formation) capped by 400 m of alluvial fan conglomerates (middle Miocene upper Tinajani Formation). New U‐Pb zircon chronostratigraphic constraints from 30 to 15 Ma yield sediment accumulation rates of 110–660 m/Myr. Newly dated growth strata highlight the genetic role played by thrust displacement in basin evolution. A several phase accumulation history derived from chronostratigraphic, provenance, and structural data reveals Oligocene basin filling by fluvial sand and mud that changes provenance from Western Cordillera Mesozoic‐Cenozoic volcanic rocks to Paleozoic‐Mesozoic Eastern Cordillera sedimentary rocks driven by deformation along the southwest directed, northeastern basin margin Ayaviri thrust at 28–26 Ma. Continued early Miocene fluvial deposition was sourced solely from the Eastern Cordillera. An abrupt middle Miocene shift to coarse alluvial fan deposition sourced from the Western Cordillera was driven by out‐of‐sequence deformation along the northeast directed, southwestern basin margin Pasani thrust at 18–16 Ma. This northern Altiplano out‐of‐sequence deformation was coincident with increased Eastern and Western Cordillera exhumation and thrusting and may be symptomatic of changes in critical wedge dynamics. The overall record of basin sedimentation and syndepositional fold‐thrust deformation emphasizes the role of regional shortening in governing crustal thickening and basin evolution in the central Andes during the Oligocene to Miocene.